Overview of Celiac Disease in Russia: Regional Data and Estimated Prevalence - Lyudmila V. Savvateeva; Svetlana I. Erdes; Anton S. Antishin; Andrey A. Zamyatnin (Journal of Immunology Research)
Celiac disease (CD) is an autoimmune enteropathy triggered by the ingestion of dietary gluten from some cereals mainly in individuals carrying the HLA-DQ2 and/or HLA-DQ8 haplotypes. As an autoimmune disease, CD is manifested in the small intestine in the form of a progressive and reversible inflammatory lesion due to immune response to self-antigens. Indeed, CD is one of the most challenging medicosocial problems in current gastroenterology. At present, the global CD prevalence is estimated at approximately 1% based on data sent from different locations and available CD screening strategies used. However, it is impossible to estimate global CD prevalence without all the data from the world, including Russia. In this review, we summarize the data on the incidence and prevalence of CD across geographically distinct regions of Russia, which are mostly present in local Russian scientific sources. Our conclusion is that the situation of CD prevalence in Russia is higher than is commonly believed and follows global tendencies that correspond to the epidemiologic situation in Europe, America, and Southwest Asia.